2020
DOI: 10.1016/j.annonc.2020.08.2114
|View full text |Cite
|
Sign up to set email alerts
|

CN10 Cancer nursing education and recognition in Europe: A survey by the European Oncology Nursing Society

Abstract: Background: Prior research by the European Oncology Nursing Society (EONS) has provided evidence for significant differences in various dimension of cancer nursing across Europe. EONS Advocacy working group has developed the European Cancer Nursing Index (ECNI) to illustrate the status and better promote cancer nursing among political and/or health contexts.Methods: Data on education and career development, patient and occupational safety, working conditions and impact, recognition and workforce statistics) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recent oncology nursing education reviews and literature include a survey by the European Oncology Nursing Society [2020] on European cancer nursing education and recognition (9) and a survey on European geriatric oncology nursing education [2021] (10). The first survey had a low response rate (~25%) and the authors found that despite oncology nursing education in some countries beginning as early as the 1980s, only five national governments recognized this specialty.…”
Section: Rationale and Knowledge Gapmentioning
confidence: 99%
“…Recent oncology nursing education reviews and literature include a survey by the European Oncology Nursing Society [2020] on European cancer nursing education and recognition (9) and a survey on European geriatric oncology nursing education [2021] (10). The first survey had a low response rate (~25%) and the authors found that despite oncology nursing education in some countries beginning as early as the 1980s, only five national governments recognized this specialty.…”
Section: Rationale and Knowledge Gapmentioning
confidence: 99%
“…A survey done in 2019 by the European Oncology Nurses Society of hospitals across Europe revealed that only 5/13 responding countries had specialty recognition for oncology nurses in general, thus the pediatric oncology nurse specialization is also lagging. 12 In China, the Ministry of Health 2010-2015 document issued a training outline (2-3 months) for five nursing specialties including oncology nursing. 9 One aim of the Chinese Nursing Association, with 24 specialty societies (including pediatric and oncology] is to address nursing professional competence.…”
mentioning
confidence: 99%